Analysis of the Utilization of AI ChatGPT in Assisting the Learning Process of Informatics Education Students at Citra Bangsa University - Hendrik, Felsita Natalia; Sogen, Maria Magdalena Beatrice; Baidenggan, Wulan Marsela; Do'o, Faldi (JUPE : Jurnal Pendidikan Mandala, 2025)
This study aims to analyze the utilization of Artificial Intelligence (AI) technology, specifically ChatGPT, in assisting the learning process of students in the Informatics Education study program. The research focuses on the following issues: the level of ChatGPT utilization by students during their learning activities; the benefits experienced from using ChatGPT as a tool to understand material, debug code, and complete assignments; and students’ perceptions of the effectiveness of ChatGPT in enhancing their understanding of Informatics coursework.The method used in this study refers to a quantitative approach with a survey method, employing data collection through the distribution of structured questionnaire instruments to research participants, namely active students of the Informatics Education Study Program. Out of 30 respondents, 96.7% use ChatGPT, primarily to understand material, complete assignments, and engage in independent learning. Students identified various functional benefits from using ChatGPT, such as increased study time efficiency, ease in obtaining conceptual clarifications, and the ability to access explanations that are more structured and easier to understand compared to conventional sourcesFurthermore, most students gave positive evaluations of ChatGPT as a digital entity capable of increasing learning motivation, improving material comprehension, saving time, and supporting practical tasks. These findings confirm ChatGPT’s potential as an effective learning support tool. However, its integration needs to be conducted wisely to avoid cognitive dependency and maintain academic integrity.Based on the overall findings presented, this study recommends that the use of ChatGPT in higher education contexts be done proportionally, prudently, and accompanied by a critical attitude. Students are encouraged not to passively accept every piece of information provided by the AI system but rather to use it as an intellectual stimulus to explore further knowledge, develop deeper understanding, and uphold academic integrity in every learning process.